An Increased Understanding of Enolate Additions under Mechanochemical Conditions - Heather Hopgood; James Mack (Molecules, 2017)
Very little is known about enolate addition chemistry under solver-free mechanochemical conditions. In this report, we investigated the ability to selectively form products arising from the primary, secondary, and tertiary enolates under solvent-free conditions. Using potassium tert-butoxide as the base and primary, secondary, and tertiary electrophiles, we were able to generate various enolate addition products including, 1,3,3,3-tetraphenyl-2,2-dimethyl-1-propanone; a molecule we did not observe under traditional solution-based conditions.